Peningkatan Pendapatan UMK Melalui Pelatihan Penentuan Harga Pokok Produksi - Emaya Kurniawati; Sri Yuni Widowati; Aprih Santoso (IAI Darussalam, 2018)
The livelihoods of the Cepiring District of Kendal Regency are mostly in the agricultural sector, the second and third are the manufacturing industry and the trade, hotel, and restaurant sector. Micro Small Enterprises (MSEs) in Cepiring Kendal District numbered 35 people. This training main objective is to equip by training MSE entrepreneurs with the knowledge of how to determine the cost of production right in order to increase their business income. The results of the training showed that MSE entrepreneurs in Cepiring Kendal District were able to make a simple determination of the Basic Price of Orders and Pricing Prices. The UMK entrepreneurs in Cepiring District Kendal responded positively to the training. This positive response can be seen from the enthusiasm of the participants in the discussion session or during practice, even the participants want advanced training and mentoring. Key Words: SMEs, Orders, Processes, Income